1997
DOI: 10.1523/jneurosci.17-16-06086.1997
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation at a Single Site in the Rat Brain Sodium Channel Is Necessary and Sufficient for Current Reduction by Protein Kinase A

Abstract: Voltage-gated sodium channels respond to excitatory inputs in nerve cells, generating spikes of depolarization at axon hillock regions and propagating the initial rising phase of action potentials through axons. It previously has been shown that protein kinase A (PKA) attenuates sodium current amplitude 20-50% by phosphorylating serines located in the I-II linker of the sodium channel. We have tested the individual contributions of five PKA consensus sites in the I-II linker by measuring sodium currents expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
82
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 22 publications
(33 reference statements)
10
82
0
Order By: Relevance
“…Changes in synaptic excitation of two motoneurons (termed aCC and RP2) are compensated for by altered membrane excitability primarily mediated through changes in I Na (Baines et al, 2001;Baines, 2003). Activity-dependent regulation of the cAMP-protein kinase A (PKA) pathway is both necessary and sufficient to mediate rapid changes in I Na in aCC/RP2 (Baines, 2003), consistent with in vitro studies that show phosphorylation of rat Na ϩ channels to be an effective determinant of channel conductance (Li et al, 1992;Smith and Goldin, 1997;Catterall, 2000). However, whereas rapid change in I Na is predicted to compensate for equally rapid fluctuations in synaptic excitation, longer-term changes in neuronal activity might be better compensated for by changes in gene expression.…”
Section: Introductionsupporting
confidence: 54%
“…Changes in synaptic excitation of two motoneurons (termed aCC and RP2) are compensated for by altered membrane excitability primarily mediated through changes in I Na (Baines et al, 2001;Baines, 2003). Activity-dependent regulation of the cAMP-protein kinase A (PKA) pathway is both necessary and sufficient to mediate rapid changes in I Na in aCC/RP2 (Baines, 2003), consistent with in vitro studies that show phosphorylation of rat Na ϩ channels to be an effective determinant of channel conductance (Li et al, 1992;Smith and Goldin, 1997;Catterall, 2000). However, whereas rapid change in I Na is predicted to compensate for equally rapid fluctuations in synaptic excitation, longer-term changes in neuronal activity might be better compensated for by changes in gene expression.…”
Section: Introductionsupporting
confidence: 54%
“…L2 of NaN shows only 18% similarity to L2 of SNS͞PN3. These loops contain predicted phosphorylation sites that have been shown to modulate Na currents (55,56). The different sequence of these loops in NaN and SNS͞PN3 suggests that NaN may be regulated͞modulated differently than SNS͞PN3 in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of PKA reduced fast Na ϩ current, but did not change its activation or inactivation (Schiffmann et al 1995;Smith and Goldin 1997;Zhang et al 1998). In PFC neurons, voltage-clamp studies of the effects of dopamine on the transient fast Na ϩ current have not been reported.…”
Section: Ionic Mechanisms That Regulate Spike Firing Threshold In Pfcmentioning
confidence: 99%
“…2 (Calabresi et al 1987; Cépeda et al 1992b;Hernández-López et al 1997). Brain Na ϩ channels are modulated via either phosphorylation by protein kinase C (PKC) and protein kinase A (PKA) (Numan et al 1991;Smith and Goldin 1997). Activation of PKA reduced fast Na ϩ current, but did not change its activation or inactivation (Schiffmann et al 1995;Smith and Goldin 1997;Zhang et al 1998).…”
mentioning
confidence: 99%